Drivers of soil temperature variation in alpine lichen heaths and shrub vegetation during the summer - Peter Aartsma; Arvid Odland; Stefanie Reinhardt; Hans Renssen (Arctic, Antarctic, and Alpine Research, 2023)
Lichen heaths are decreasing in abundance in alpine and Arctic areas because of an increased competition with shrubs. This shift in vegetation might have important consequences for the soil temperature. The aim of this study is to find the drivers of the variation in soil temperature below lichen heaths and shrubs. Moreover, we want to gain more insight in the variability of the soil temperature below lichen heaths. We measured the soil temperature in thirty lichen plots and fifteen shrub plots in an alpine area in southern Norway during July and August 2019. We applied several treatments to study the drivers behind the variation in soil temperature between lichen heaths and shrub vegetation. We found that the average soil temperature was 1.45°C higher below lichen heaths than below shrub vegetation. Moreover, we measured a difference in soil temperature of 1.66°C between north- and south-facing lichen heaths, which contributes to the small-scale spatial variability in soil temperature below lichen heaths. Based on our experiments, we conclude that the buffering capacity of the litter layer below shrubs and shading of the soil by the shrub canopy lead to a lower soil temperature below shrubs compared to lichen heaths during the summer.